190k views
3 votes
3[x + 4(6 - x) + 24] - 11 = 61 - 12x

User Deep Verma
by
4.9k points

2 Answers

4 votes

Answer:

x = -24

Explanation:


3[x+4(6-x)+24]-11=61-12x

Expand:


3(x+24-4x+24)-11=61-12x

Simplify:


3(-3x+48)-11=61-12x

Expand again:


-9x+144-11=61-12x

Simplify:


-9x+133=61-12x

Subtract 133 from both sides:


-9x=61-12x-133


-9x=-12x-72

Add 12x to both sides:


3x=-72

Divide 3:


x=-24

User MahanGM
by
4.8k points
4 votes

Answer:

-24

Explanation:

3(x+24-4x+24)-11=61-12x

3(-3x+48)-11=61-12x

-9x+144-11=61-12x

-9x+12x=61-144+11

3x=-72

divide both sides by 3

3x/3=-72/3

x=-24

User Venkat
by
4.6k points